Influence of the polarity of the matrix on the breakage mechanisms of lignocellulosic fibers during twin‐screw extrusion. Issue 3 (20th November 2019) - Berzin, Françoise; Lemkhanter, Loubna; Marcuello, Carlos; Chabbert, Brigitte; Aguié‐Béghin, Véronique; Molinari, Michael; Castellani, Romain; Vergnes, Bruno
Abstract: In a series of previous papers, models describing the breakage of lignocellulose fibers during melt mixing process were established and applied to predict fiber size changes when compounding composites in a twin‐screw extruder. Different types of fibers were studied (flax, hemp, sisal, etc), but always with the same matrix, namely polypropylene (PP) compatibilized with PP grafted with maleic anhydride (PP‐g‐MA). In the present study, the influence of the matrix was characterized, by comparing the results obtained with nonpolar PP and polar poly(butylene succinate) (PBS) of similar viscosity. For flax and hemp fibers, morphology changes (in length and diameter) were characterized along the screws under various processing conditions (screw speed and feed rate). Whatever the conditions, breakage was more important with the PBS matrix. Moreover, the rheological properties of the composites were also different, indicating specific interactions between fibers and matrices. Atomic force microscopy was used to measure the adhesion between the different matrices and AFM levers functionalized with nanocrystalline cellulose. The results confirmed a better interaction between the nanocrystalline cellulose and the PBS matrix compared to the PP one.